Airway management in a patient of ankylosing spondylitis with traumatic cervical spine injury - Nilesh Kumar; Ashish Bindra; Charu Mahajan; Naveen Yadav (Saudi Journal of Anaesthesia, 2015)
Traumatic cervical lesions compressing the spinal cord pose a significant risk of exacerbating the existing neurological condition during tracheal intubation and subsequent positioning. Preexisting ankylosing spondylitis with spinal column involvement renders the spinal column more rigid and introduces difficulty in airway management of the patient with traumatic cervical spinal cord. To improve ease and success, and reduce cervical spine movement, awake fibreoptic intubation (FOI) is considered the gold standard technique for airway management in such cases. Attaining appropriate position for intubation was challenge in this case due to rigid curvature of the ankylosed spinal column. To prevent neurological injury to the spinal cord and preserve spinal cord function, minimizing movement during intubation and attaining appropriate position was of prime concern. Optimal sedation with self-positioning by the patient in a comfortable posture is quite imperative and assures both airway as well as neurological protection in such expected difficult situations. We report the use of dexmedetomidine for self-positioning and awake FOI in a patient with ankylosing spondylitis having traumatic cervical spine who was otherwise neither able to co-operative nor able to give appropriate position for FOI.